Effect of sp3/sp2 Ratio on Boron Doped Diamond Films for Producing Persulfate. (1st January 2015) - Barreto, Jéssica Pires de Paiva; Araújo, Karla C. de Freitas; de Araújo, Danyelle Medeiros; Martínez-Huitle, Carlos A.
Abstract : The role of the influence of sp 3 /sp 2 ratio for producing persulfate (S2 O8 2− ) was investigated for the first time at boron doped diamond (BDD) electrodes with significant differences on diamond content. Results clearly pointed out that diamond with a very lower sp 3 /sp 2 ratio promotes an improvement on the production of S2 O8 2− of about 50% at high current densities when compared with BDD with higher diamond content. From a practical application perspective, this novel result provides a guideline for designing diamond electrodes for environmental approaches.